Startup strategies in building brand awareness: (Roland Barthes' semiotic analysis of Korean drama Start-Up) - Amalia, Bella; Fatimah, Anggun Nadia; Rizki, Menati Fajar; Sari, Wina Puspita; El Farabi, Qoryna Noer Seyma (Priviet Social Sciences Journal, 2025)
Digital technology development has driven the rapid growth of startups in Indonesia. In increasingly fierce competition, brand awareness strategies are key to strengthening identity and attracting the attention of the public and investors. One way to understand and inspire this strategy is through the analysis of representations in popular media, such as Korean dramas, which have broad appeal and influence. This study aims to analyze Samsan Tech's brand awareness strategy in Start-Up dramas using the Attention, Interest, Desire, Action (AIDA) model, as well as examine its symbolic meaning through Roland Barthes' semiotics. This study uses a qualitative approach with content analysis and semiotics methods to explore the meaning of denotative, connotative, and mythical. Data were collected through observation and scene documentation featuring brand awareness strategies, and supported by literature reviews related to AIDA models and startup communication strategies. The results show that Samsan Tech applied the AIDA model by attracting attention through competition, building interest through product presentations, creating desires through relationships with public figures and business projections, and encouraging action through cooperation with large investors. Barthes' analysis reveals symbolic meanings, such as entrepreneurial spirit, team collaboration, and the struggle to face business challenges. This study shows that popular dramas can represent an inspiring business strategy and shape the public perception of startups.